Design-Time Web Usability Evaluation with Guideliner - Jevgeni Marenkov; Tarmo Robal; Ahto Kalja (Complex Systems Informatics and Modeling Quarterly)
The diversity of smartphones and tablet computers has become an integral part of modern life. An essential requirement for web application development is following web usability guidelines, while designing web user interface (UI). Even a minor change in UI could lead to usability problems. Empirical evaluation methods like interviews and questionnaires with user-tests and card sorting are effective in finding such problems. Nevertheless, there are multiple obstacles preventing the application of these methods especially for evaluating minor UI changes, for instance, due to the time and human-resources they require, and the amount of data to be processed. The purpose of this current publication is to present Guideliner – a tool for implementation-time automatic evaluation of web UI conformance to predefined usability guidelines. The main contribution of the presented solution is enabling immediate cost-efficient and automated web UI evaluation that conforms to available and set standards.